Muon Bremsstrahlung and Muonic Pair Production in Air Showers - Cillis, Analía Nilda (2001)
The objective of this work is to report on the modifications in air shower development due to muon bremsstrahlung and muonic pair production. In order to do that we have implemented new muon bremsstrahlung and muonic pair production procedures in the AIRES air shower simulation system, and have used it to simulate ultra high energy showers in different conditions. The influence of the mentioned processes in the global development of the air shower is important for primary particles of large zenith angles, while they do not introduce significant changes in the position of the shower maximum.